Molecular Epidemiology of Human Papilloma Virus (HPV) in Women’s Cervical Samples from Tehran, Iran - Kashefi, Fatemeh; Alizadeh, Mitra; Sadat Kalaki, Niloufar; Ejlalidiz, Mahsa; Yazdani, Shaghayegh; Shayestehpour, Mohammad; Farsi, Mahsa; Emtiazi, Nikoo; Hemmasi, Gholamreza; Karbalaie Niya, Mohammad Hadi (Asian Pacific Journal of Cancer Biology, 2024)
Background: Cervical cancer (CC) is the second-leading cause of cancer death among women. In this cancer, more than any other type of malignancy, the effects of prevention, early diagnosis, and timely treatment on reducing the death rate are evident. Hence the aim of this study was to Investigating the prevalence of human papilloma virus different genotypes in women’s cervical tissue samples. Methods: In this cross-sectional study, 1045 samples obtained from referred patients were selected for periodic cervical examinations. Then, DNA extraction from cytology liquid brush was done in accordance with the standard method. The presence of HPV was determined by PCR. By using pyrosequencing method and then BLAST online search, HPV genotypes were identified. Results: of 1045 patients, 159 (15%) had HPV infection in which 50.3% were LSIL by frequent HPV types 6, 18, 16, 11; 19.4% were HSIL by frequent HPV types 16, 18, and 30.1% were ASCUS by frequent HPV types 6, 11, respectively. The age group, 30–40 years had the highest prevalence of HPV infection (p-value = 0.6). 21.4% people diagnosed by mix genotype HPV infection. significant value identified by the pathological patterns and multiple types infections (p-value=0.007), HPV-16 infection and younger age (p-value=0.02). Conclusion: our study showed 15% HPV infection identified in studied samples and the most HPV prevalent types were 6, 18, 11, 16, respectively. HPV-16 is common in younger ages. HPV vaccination and regular screening programs are major prevention measures.